Reproductive potential of the endangered land crab, Johngarthia lagostoma (H. Milne Edwards, 1837) (Brachyura: Gecarcinidae), from Trindade Island, Brazil - Esli E. D. Mosna; Maria A. M. Oliveira; Marcio C. A. João; Marcelo A. A. Pinheiro (Nauplius)
Abstract An analysis of reproductive potential can elucidate significant aspects of the population biology and evolution of brachyuran crabs, providing a crucial baseline for conservation efforts concerning endangered species. Johngarthia lagostoma is an endemic species to Atlantic Oceanic islands (Rocas Atoll, Fernando de Noronha, Ascension, and Trindade), and it is classified as endangered (EN) in Brazilian territory according to IUCN criteria. Until now, the reproductive potential of this species has only been described for the Ascension Island population. Therefore, we assessed the reproductive effort and fecundity of J. lagostoma on Trindade Island. A total of 43 ovigerous females in the final stage of embryonic development were analyzed. Their egg masses were removed, weighed, and counted using a volumetric method. The carapace width ranged from 55.3 to 100.1 mm (mean ± standard deviation: 75.2 ± 13.1 mm). It exhibited a good fit and positive correlation with the egg weight and fecundity data but a poor fit and negative correlation with reproductive effort. The contrasting results of fecundity (82,938 ± 43,673 eggs) and reproductive effort (10.5 ± 1.5 %) recorded for J. lagostoma reveal a well-established population on Trindade Island compared to Ascension Island. These observations provide valuable information for proposing more effective management strategies for this endangered species across these Atlantic oceanic islands.